Some interesting and new records of leaf beetles (Coleoptera: Chrysomelidae) from Pakistan - Ahmed, Zubair; Lalika, Haseeb Ahmed (Baltic Journal of Coleopterology, 2024)
We have studied 16 species of Chrysomelidae with distribution notes. Seven species were recorded for the first time in the country. These species encompass four subfamilies: Alticinae, Chrysomelinae, Cryptocephalinae, and Galerucinae. The list includes eight species, four subspecies, and three at the genus level: Entomoscelis adonidis; Gastrophysa polygoni polygoni Linnaeus, 1758; Clytra (Clytraria) afghanica Reineck, 1937; Clytrasoma conformis, Lacordaire, 1848; Clytrasoma palliata Fabricius, 1801; Madurasia undulatovittata (Motschulsky, 1866); Monolepta sexlineata Chujo, 1938; Hermaephaga (Orthocrepis) ruficollis (Lucas, 1847); Nonarthra variabilis Baly, 1862; Chrysolina caerulans bella Jacoby, 1890; Clytra atraphaxidis atraphaxidis (Pallas, 1773); Miochira signaticollis signaticollis (Kollar & L. Redtenbacher, 1844); Theone octocostata cf. woehrli; Chrysolina (Bittotaenia) cf. mellyi (Stal, 1857); and Diapromorpha cf. turcica Fabricius, 1801. Seven species and four subspecies have been recorded for the first time, while three subspecies are closely related. The other three species are interesting with their new distribution.